Cultural assimilation, cultural diffusion and the origin of the wealth of nations - Quamrul Ashraf; Oded Galor (Brown University, Department of Economics, 2007)
This research argues that variations in the interplay between cultural assimilation and cultural diffusion have played a significant role in giving rise to differential patterns of economic development across the globe. Societies that were geographically less vulnerable to cultural diffusion, benefited from enhanced assimilation, lower cultural diversity and, thus, more intense accumulation of society-specific human capital, enabling them to flourish in the technological paradigm that characterized the agricultural stage of development. The lack of cultural diffusion and its manifestation in cultural rigidity, however, diminished the ability of these societies to adapt to a new technological paradigm, which delayed their industrialization and, thereby, their take-off to a state of sustained economic growth. The theory contributes to the understanding of the advent of divergence and overtaking in the process of long-run development, attributing the dominance of some societies within a given technological regime to a superior operation of cultural assimilation, while the success of others in the switch between technological regimes to a higher frequency of cultural diffusion and the beneficial effect of diversity on the adaptability of society to a changing technological environment. Thus, in contrast to the cultural and institutional hypotheses, which posit a hierarchy of cultural and institutional attributes in terms of their conduciveness to innovation and their ability in fostering industrialization, the proposed theory suggests that the desirable degree of the relative prevalence of cultural assimilation versus cultural diffusion varies according to the stage of development. Enhanced cultural assimilation is optimal within a given stage of development, but is detrimental for the transition between technological regimes. Therefore, while cultural traits themselves do not necessarily have a differential effect on the process of development, it is the variation in the relative strengths of the forces of cultural assimilation and cultural diffusion, which together determine the heterogeneity of these traits, that is instrumental for comparative economic development.
Keywords: O11; O13; O14; O31; O33; O41; O43; 330; Cultural assimilation; Cultural diffusion; Cultural diversity; Geography; Economic development; Agriculture; Industrialization; Wirtschaftswachstum; Entwicklung; Internationale Wanderung; Kulturelle Beziehungen; Sozialer Wandel; Soziale Integration; Humankapital; Wirtschaftskultur; Wirtschaftsgeschichte; Welt